Spirituality of place and its relationship to job performance of public-school principals in Jerusalem governorate from their point of view - Abu Sarhan, Lubna Mousa; Olyan, Ayoub Mousa; Makhamra, Kamal Khalil (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the spirituality of the place and its relationship to the job performance of public-school principals in Jerusalem governorate from their point of view, by knowing the level of spirituality of the place and the level of job performance of school principals, and the relationship between them, and knowing the statistically significant differences for a group of variables. To achieve the objectives of the study, the researchers used the descriptive, correlational survey method, and the questionnaire as a tool for collecting data from a sample of 96 male and female principals, representing 76.8% of the study population. And to a very high degree, and at the level of fields; Purposeful work obtained the highest average (4.36), then the individual’s values corresponded to the values of the organization (4.32), both with a (very high) degree, thirdly, the sense of group (4.20), and fourthly, the workplace (4.12), both with a (high) degree, with a percentage of (85.1%). And that their level of job performance obtained an overall average of (4.31 out of 5) with a (very high) degree, with a percentage of (86.2%). And that the value of the relationship between the spirituality of the place and the job performance of the public- school principals in the Jerusalem governorate according to the Pearson correlation coefficient was (0.608), (moderate positive) and that the higher the level of the spirituality of the place among the public-school principals in the Jerusalem governorate, the higher the level of their job performance. While there were no differences in the estimates of the respondents in the spirituality of the workplace or in job performance according to the variables (gender, number of years of total service, service in administration, qualification, and directorate), the researchers recommended the need to strengthen the education environment and education management in all governorates, to enhance education Palestinian and achieve the goals of the institution.
Keywords: spirituality of place; job performance; government schools; Jerusalem